Involvement of endoplasmic reticulum stress-induced apoptotic pathway in cervical cancer cells treated with cytotoxic agents - Wan Abd Ghani, Wan Nor Hafiza (2014)
Cervical cancer is one of the most common cancer in women. Cisplatin is used to treat cervical cancer but it has adverse effects. Therefore, prediction of chemosensitivity or response towards any drug based on certain biomarkers is vital. Glucose regulated protein (GRP58) is predicted to become the potential biomarker or prognostic marker. This study investigated the response of human cervical cancer cells to cisplatin, thymoquinone (TQ), ethyl acetate and dichloromethane extracts of Dillenia suffruticosa root (EADS and DCMDS) based on the expression of GRP58 at gene and protein level which was measured by RT-qPCR and Western blot, respectively. The effects of EADS and DCMDS on the growth of HeLa and SiHa cervical cancer cell lines and expression of apoptotic-related genes and proteins were also investigated. Cytotoxicity was determined by MTT assay. The effects on cell cycle progression and mode of cell death of EADS were analyzed by flow cytometry technique. The effects on expression on apoptotic-related genes and proteins were evaluated by RT-qPCR, Western blot and ELISA, respectively. Cisplatin was more cytotoxic towards the cells than TQ in a dose-and time-dependent manner (P<0.05). However, cisplatin was more toxic to the normal cell lines 3T3 and Vero than TQ. Significant correlation was only found between cytotoxicity of cisplatin towards the cervical cancer cells and the expression of GRP58 (P<0.05). Therefore, the response of cervical cancer cells to cisplatin can be predicted on the basis of GRP58. Meanwhile, EADS and DCMDS were found to significantly (P<0.05) inhibit cell growth and proliferation of HeLa and SiHa. DCMDS was more cytotoxic towards the cells than EADS in a dose-and time-dependent manner. DCMDS caused downregulation of the expression of cyclin B1 that led to G2/M arrest in the cells. DCMDS induced apoptosis as evidenced by Annexin-V/FITC assay. DCMDS induced apoptosis in the cervical cancer cells via dysregulation of mitochondrial-mediated and ER stress-induced apoptotic pathways. DCMDS triggered the extrinsic apoptotic pathway via activation of caspase-8. Meanwhile, the intrinsic apoptotic pathway was triggered upon activation of PARP-1, NF-κB, p53 and JNK. Increased expression of Bax, but decreased expression of Bcl-2 further enhanced the release of cytochrome C and increased in caspase-3 and -9 activities which ultimately led to apoptosis. DCMDS also upregulated ER stress genes chaperones GRP78 and CRT; and ER transcription factors CHOP/GADD153, XBP-1 and ATF4. Nevertheless, the level of GRP58 reduced in a dose-dependent manner. The number of apoptotic cells increased as the concentration of DCMDS increases. Thus, GRP58 might play a role in DCMDS-induced ER stress-induced apoptosis since other ER stress proteins were upregulated but only GRP58 level was downregulated. The data suggest the potential application of DCMDS in the treatment of cervical cancer.